2019
DOI: 10.1364/jocn.11.000354
|View full text |Cite
|
Sign up to set email alerts
|

Connected OFCity Challenge: Addressing the Digital Divide in the Developing World

Abstract: The development of Information and Communications Technology has provided over the past 50 years unprecedented support to the steady economic growth of developed countries. In recent years, some of the largest growths have been reported in emerging economies, which however often lack adequate telecommunications infrastructure to further sustain their development. Although a number of service and vendor providers have started to address the issue, the challenges they encounter are substantially different from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…This process adheres to the strict requirements of Data Center Interconnects (DCIs) [9]. A study by Ruffini et al reported a state-of-the-art passive optical network (PON) technology (NG-PON2) [10]. The study effectively performed the convergence process in a single PON infrastructure.…”
Section: Related Workmentioning
confidence: 95%
“…This process adheres to the strict requirements of Data Center Interconnects (DCIs) [9]. A study by Ruffini et al reported a state-of-the-art passive optical network (PON) technology (NG-PON2) [10]. The study effectively performed the convergence process in a single PON infrastructure.…”
Section: Related Workmentioning
confidence: 95%
“…It exists also in some of the largest growing and emerging economies where adequate infrastructures are not available. Cases in Africa and rural China have been studied in this regard and innovative solutions are possible, whether for green-field scenarios or for others where legacy-copper infrastructures may be upgraded [10].…”
mentioning
confidence: 99%